The effect of informal caregiving on medication: evidence from administrative data - Magdalena Stroka-Wetsch (The European Journal of Health Economics, 2022)
This study evaluates the mental and physical strain experienced by informal caregivers. Econometric problems due to individuals selecting themselves into informal care provision are tackled using informative and detailed data on more than 2 million insureds from the largest sickness fund in Germany and applying the propensity score matching technique to estimate the average effect of treatment on the treated. This effect indicates how carers have fared relative to a counterfactual situation in which they would have been non-carers. The radius matching is applied in combination with a strict caliper to obtain a high degree of observational similarity between caring and non-caring individuals. The findings suggest that carers take more psychoactive drugs as well as analgesics and gastrointestinal agents. Females consume about 5 daily defined doses of antidepressants more when they care for dependent relatives. In case of tranquilizers and analgesics, the estimated effect for females amounts about 1 daily defined dose. Considering gastrointestinal agents, the effect amounts to 2 daily defined doses. Thus, informal caregiving appears to be a burdensome task with implications for both mental and physical health.
Keywords: I10; 610; Informal care; Burden; Drugs; Propensity score matching